Optoelectronic Devices: Wafer‐Scale Highly Ordered Anodic Aluminum Oxide by Soft Nanoimprinting Lithography for Optoelectronics Light Management (Adv. Mater. Interfaces 5/2017). Issue 5 (March 2017) - Zhang, Chi; Li, Wenchao; Yu, Dongliang; Wang, Yanshan; Yin, Min; Wang, Hui; Song, Ye; Zhu, Xufei; Chang, Paichun; Chen, Xiaoyuan; Li, Dongdong
Abstract : D. Li, P. Chang and co‐workers present the largearea highly ordered porous anodic aluminum oxide (HOAAO) membranes based on full‐field nanoimprinting lithography using soft stamps and electrochemical anodization in article number 1601116. The porous films with straight nanochannels and inverted nanocones are rationally obtained via finely tuned electrochemical anodization. In addition, the large area HOAAO films with tunable nanostructures can provide a versatile platform for high‐performance optoelectronic devices.